2015
DOI: 10.5942/jawwa.2015.107.0129
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐Use Devices for Attenuation of Trace Organic Compounds in Water

Abstract: Trace organic compounds (TOrCs) continue to be detected in drinking water, and their recalcitrance makes them difficult to attenuate without installing expensive advanced treatment processes. Because human consumption is a small portion of net household water use, point‐of‐use (POU) devices may provide additional security against drinking water contaminants. This research evaluated three pitcher and two refrigerator POU devices using two waters. Refrigerator POU devices removed more TOrCs over the manufacturer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Three of the 4 studies of organic contaminants we reviewed examined the effectiveness of POU filters in reducing levels of disinfection by-products (DBPs), including THMs, in drinking water. [23][24][25] Anumol et al 26 examined removal efficiencies for 16 individual trace organic compounds (TORCs), including pharmaceuticals, pesticides, and other organic contaminants, by 2 refrigerator SBAC POU devices and a commercially available activated carbon pitcher. This study evaluated POU performance over the life of the filters and found that all were effective in reducing levels of TORCs initially by 70 to >90%.…”
Section: Organic Contaminantsmentioning
confidence: 99%
“…Three of the 4 studies of organic contaminants we reviewed examined the effectiveness of POU filters in reducing levels of disinfection by-products (DBPs), including THMs, in drinking water. [23][24][25] Anumol et al 26 examined removal efficiencies for 16 individual trace organic compounds (TORCs), including pharmaceuticals, pesticides, and other organic contaminants, by 2 refrigerator SBAC POU devices and a commercially available activated carbon pitcher. This study evaluated POU performance over the life of the filters and found that all were effective in reducing levels of TORCs initially by 70 to >90%.…”
Section: Organic Contaminantsmentioning
confidence: 99%
“…The occurrence of these compounds was observed in influent, effluent of sewage treatment plants and hospital, and surface water in Malaysia with concentration of metoprolol ranged from 25 to 364 ng/L [1][2][3]. Some studies have reported the abundance of drugs in groundwater, urban wastewater plants, rivers, hospital wastewater and lakes around the world, however, the median of metoprolol in river was 52 ng/L [4][5][6][7]. Although, the concentration of these pollutants is low in the environment, these pharmaceuticals may pose adverse effects on the organisms and humans due to long-term exposure [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated for various chemical classes, including perfluorinated chemicals, that drinking water can be one of the most important pathways for human exposure . Even so, it has been estimated that only 40% of US consumers used any kind of water purification device in 2014 (Anumol et al, 2015). Certain chemicals are regulated under the Safe Drinking Water Act, but these chemicals constitute only a small fraction of the number of chemicals present in drinking water (US EPA, 2016).…”
Section: Introductionmentioning
confidence: 99%